Effects of doping elements in β-FeSi2 prepared utilizing cast iron scrap chips - Nor Hairin, Assayidatul Laila; Nanko, Makoto; Takeda, Masatoshi (Japan Institute of Metals (JIM), 2016)
In this work, the thermoelectric properties of p- and n-type β-FeSi2, prepared utilizing cast iron scrap chips, have been characterized by measuring the Seebeck coefficient, electrical conductivity and thermal conductivity at temperatures ranging from room temperatures to 800°C. In a previous study, the upgrade recycling of cast iron scrap chips into β-FeSi2 thermoelectric materials was proposed as an eco-friendly and costeffective production process. By doping with different substitution concentrations of Co, Mn and Al, the conduction type and properties of β-FeSi2 can be modified and improved using cast iron scrap chips as a starting material. The effects of the doping elements are discussed for preparing β-FeSi2 utilizing cast iron scrap chips. Cast iron scrap chips could be preferable as a starting material to replace pure Fe for n- and ptype β-FeSi2 thermoelectric materials. An optimum composition for n-type β-FeSi2 0.94C.I.-0.06Co-1.86Si shows that the largest ZT value of 0.22 occurs at 700°C, whereas for p-type β-FeSi2 0.92C.I.-0.08Mn-1.86Si, the largest ZT value of 0.17 occurs at 800°C.